2007
DOI: 10.3197/096734007780473492
|View full text |Cite
|
Sign up to set email alerts
|

Using Oral History and Forest Management Plans to Reconstruct Traditional Non-Timber Forest Uses in the Swiss Rhone Valley (Valais) Since the Late Nineteenth Century

Abstract: Changes in forest use are considered as a potential key driver for recently observed changing forest dynamics in the pine forest belt of the upper Rhone valley (Canton of Valais, Switzerland). In this region, traditional non-timber forest uses, such as forest litter harvesting and wood pasture, were practised until the second half of the twentieth century. The practice of traditional non-timber forest uses led to specific environmental conditions which favoured pine as a pioneer species. With the abandonment … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
44
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 52 publications
(45 citation statements)
references
References 34 publications
1
44
0
Order By: Relevance
“…Also, details concerning historical events such as why and how they happened were occasionally absent from the literature, but could be created through the interviews (Fogerty 2001). In spite of these limitations, this study reinforces the views of previous authors that the written records and oral history interviews were both useful sources of information (Gimmi and Burgi 2007;Daley and others 2008), and its simultaneous use enabled greater insight into the establishment and management philosophies that guided the history of the Portuguese PAs.…”
Section: Discussionsupporting
confidence: 83%
See 2 more Smart Citations
“…Also, details concerning historical events such as why and how they happened were occasionally absent from the literature, but could be created through the interviews (Fogerty 2001). In spite of these limitations, this study reinforces the views of previous authors that the written records and oral history interviews were both useful sources of information (Gimmi and Burgi 2007;Daley and others 2008), and its simultaneous use enabled greater insight into the establishment and management philosophies that guided the history of the Portuguese PAs.…”
Section: Discussionsupporting
confidence: 83%
“…As mentioned by other authors, the oral history interviews were restricted to the informant's ability to remember (Gimmi and Burgi 2007;Riley and Harvey 2007). For example, in some cases, the exact details and dating of historical events were difficult for the informants to recall and had to be checked in the written accounts.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The historical records, forest inventories including maps and yearly management data, used in this study are generally of good quality and they provide detailed data on the forest structure relatively far back in time to a more detailed level than any other sources or methods can provide. These types of sources have been used for different purposes in many similar studies and have been found to be consistent and reliable for temporal interpretations of forest change (Ö stlund et al, 1997;Burgi, 1999;Axelsson and Ö stlund, 2001;Gimmi and Burgi, 2007;Gimmi et al, 2008). When using this kind of historical records it is important to consider that the forest management ideas have profoundly changed during the 20th Century and so have the forests.…”
Section: Discussionmentioning
confidence: 95%
“…in the valley bottom to the upper tree line at about 2 400 m a.s.l. These forests were chosen due to the excellent historical source availability, especially forest management plans which are a valuable source for reconstructing historic forest conditions and forest uses (Bürgi, 1999;Gimmi and Bürgi, 2007;Gimmi et al, 2009). …”
Section: Study Areamentioning
confidence: 99%